2006
DOI: 10.1002/anie.200503205
|View full text |Cite
|
Sign up to set email alerts
|

Surface versus Molecular Siloxy Ligands in Well‐Defined Olefin Metathesis Catalysts: [{(RO)3SiO}Mo(NAr)(CHtBu)(CH2tBu)]

Abstract: Surface organometallic chemistry: Similar electronic properties of molecular and surface siloxy ligands in 1 m and 1 were revealed by a structural investigation with solid‐state NMR spectroscopy and a reactivity study in olefin metathesis. Despite similar initial turnover frequencies, the silica‐supported catalyst 1 is more stable than 1 m and allows it to achieve higher turnovers, thus showing the advantage of site isolation on surfaces.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
121
1
2

Year Published

2006
2006
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 162 publications
(132 citation statements)
references
References 35 publications
8
121
1
2
Order By: Relevance
“…5 However, it has been recognised recently that activity can be higher if the X and Y ligands are different (X = CH 2 tBu, Y = OR'). [6][7][8][9][10][11] Additionally, it also has been shown that a major pathway of deactivation for homogeneous olefin metathesis catalysts is dimerization of active species. 12 Thus, generating isolated active sites through grafting is a potential approach to more stable and active catalysts.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…5 However, it has been recognised recently that activity can be higher if the X and Y ligands are different (X = CH 2 tBu, Y = OR'). [6][7][8][9][10][11] Additionally, it also has been shown that a major pathway of deactivation for homogeneous olefin metathesis catalysts is dimerization of active species. 12 Thus, generating isolated active sites through grafting is a potential approach to more stable and active catalysts.…”
mentioning
confidence: 99%
“…12 Thus, generating isolated active sites through grafting is a potential approach to more stable and active catalysts. 11 In surface organometallic chemistry, silica partially dehydroxylated at 700 °C can be considered to be a large siloxy ligands, 13,14 and therefore it constitutes a perfect entry into un-symmetric catalysts (X = CH 2 tBu, Y = OSi ). One strategy has been to use alkylidyne molecular complexes such as [M(_CCMe 3 )X 3 ] as a route to these systems through protonation of the alkylidyne ligand, [(_SiO)M(=CHCMe 3 )X 3 ].…”
mentioning
confidence: 99%
“…[16] Immobilizations on other supports have been carried out, too, [17][18][19][20] however, the actual nature of the immobilized catalyst remained unknown. The first supported chiral version of a molybdenum-based Schrock catalyst was reported in 2002, [21] …”
Section: -C 6 H 3 ]A C H T U N G T R E N N U N G (=Ch-t-bu)a C H T U mentioning
confidence: 99%
“…Mo{N[2,6-Me 2 -4(6-ClC 6 H 12 )]C 6 H 2 } 2 (CH 2 CMe 2 C 6 H 5 ) 2 (16) Compound 12 (0.740 g, 1.01 mmol) was dissolved in 100 mL of diethyl ether. The solution was cooled to À38 8C and 2 equivs.…”
Section: Mo{na C H T U N G T R E N N U N G [26-a C H T U N G T R E Nmentioning
confidence: 99%
“…Well-defined alkylidenes in high oxidation states, with electron-withdrawing ligands were identified as highly efficient metathesis catalysts [5][6][7], following the proposal by Chauvin that they were key intermediates [8,9]. Recent progress in the understanding of the structure-activity relationship, involving surface chemistry [10][11][12][13] combined with computational studies [14][15][16][17], has highlighted trends for a more rational design of alkene metathesis catalysts and shown in particular that dissymmetry at the metal center can bring about high activity. In particular, d…”
Section: Introductionmentioning
confidence: 99%